The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/adsc.200390026
|View full text |Cite
|
Sign up to set email alerts
|

Monodentate Phosphoramidites: A Breakthrough in Rhodium‐Catalysed Asymmetric Hydrogenation of Olefins

Abstract: Monodentate phosphoramidites based on BINOL or substituted BINOL are excellent ligands for the rhodium-catalysed asymmetric hydrogenation of olefins. Very high enantioselectivities were obtained with MonoPhos (7a) the simplest member of this class, a ligand that is prepared in a single step from BINOL and HMPT. Turnover numbers up to 6000 have been obtained in the hydrogenation of dehydroamino acid derivatives. Enantioselectivities in the hydrogenation of dehydroamino acids are solvent dependent; in non-protic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
82
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(94 citation statements)
references
References 95 publications
9
82
2
1
Order By: Relevance
“…For the hydrogenation of N-(1-(4-chlorophenyl) vinyl)acetamide (7e, Table 8.1) with ligand 4, the product amine 8e was produced in only 44% ee with the opposite configuration compared to the product obtained with MonoPhos ligand. In contrast, the introduction of substituents such as Br at the 6-and 6 0 -positions of MonoPhos, ligand 5, has little effect on the enantioselectivity [24].…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 97%
“…For the hydrogenation of N-(1-(4-chlorophenyl) vinyl)acetamide (7e, Table 8.1) with ligand 4, the product amine 8e was produced in only 44% ee with the opposite configuration compared to the product obtained with MonoPhos ligand. In contrast, the introduction of substituents such as Br at the 6-and 6 0 -positions of MonoPhos, ligand 5, has little effect on the enantioselectivity [24].…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 97%
“…Pizzano et al reported the synthesis of chiral biphenyl-based phosphine-phosphite ligands and evaluated their efficacy in hydrogenating N-arylimine substrates, giving up to 85% ee [77]. Although the monodentate phosphoramidite ligands such as MonoPhos (Scheme 26) have been widely used in the hydrogenation of substrates of enamides [78] and olefins [79], the search for their usefulness in Ir-catalyzed imine hydrogenation have been limited. With an additional achiral nitrogen donor such as 2,6-lutidine and acridine, Faller et al were able to prepare a cationic Ir complex of MonoPhos with BARF as the counterion.…”
Section: Phosphite Phosphinite and Phosphoramidite Ligands In Ir-bamentioning
confidence: 99%
“…[7][8][9]13 Since the early work of Reetz and Mehler, 51 Feringa and co-workers, 7,52 and Claver et al, 53 a number of new monodentate phosphorus ligands have been developed. 4,[7][8][9][10][11][12][13]54 However, newer and more efficient chiral ligands along this line are clearly needed to achieve excellent enantiopurity and high catalyst efficiency for particular substrates and reactions. We describe here the application of a new class of chiral biphenol-based monophosphite ligands 13 to the Rh(I)-catalyzed asymmetric hydrogenation of dimethyl itaconate and discussions about the possible active catalyst species.…”
Section: Asymmetric Hydrogenation Of Dimethyl Itaconatementioning
confidence: 99%